Influence of Traffic Conditions on Pedestrian Crossing Decision at Urban Street Crosswalk - Fahami, Fakhrul Amer; Basil David Daniel , (Recent Trends in Civil Engineering and Built Environment, 2025)
This study investigates pedestrian decision-making at urban roadcrossing using a mixed-methods approach, incorporating surveys, onsite observations, Exploratory Factor Analysis (EFA), and Binary Logistic Regression. Key findings reveal physical and psychosocial factors, such as the type of vehicle, presence of pedestrians, and traffic volume, significantly influence pedestrian choices. EFA identifies two major elements impacting decisions, while Binary Logistic Regression verifies their predictive potential. High traffic volume deters crossings, suggesting a need for congestion reduction, while positive coefficients for vehicle speeding, yielding behavior, and raised crosswalks encourage crossings. The study recommends evidence-based interventions, including traffic calming measures and awareness campaigns, to enhance pedestrian safety and traffic flow.